Exploring the role of Information Communication Technologies (ICTs) in a refugee population in Johannesburg, South Africa in maintaining family relationships - Coka, Thembelihle (My University, 2021)
The purpose of this research study was to explore the role that Information Communication Technologies (ICTs) play in maintaining familial relationships in a refugee population in Johannesburg, South Africa. Previous international studies have shown that refugees who are separated from their families for a myriad of reasons often desire reuniting with their families back home. One medium that they rely on to maintain family connections is through the use of ICTs. Little research has been carried out in this area with refugees living in South Africa. This study was part of a larger research project exploring the use of ICTs in different types of African migrant families. It followed a qualitative research method, using a semi-structured interview schedule to collect data from the seven refugee participants who were originally from the Democratic Republic of Congo (DRC) and have been living in Johannesburg for more than two years and had access to mobile phones. The data was analysed using Thematic Analysis. The findings identified various factors that have motivated the participants from the DRC to flee from their country of origin namely: war, persecution, torture, political and economic freedom. Once in South Africa they also experience several challenges such as Human rights violation, language barrier, lack of formal employment and financial difficulties. The refugees long for their families back home and rely on mobile phones to communicate with them. Their preferred platforms of communication are WhatsApp and Facebook. They however experience challenges related to costs of data. These factors were discussed in the study
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021